THE EFFECTIVENESS OF COLLABORATIVE LEARNING MODELS IN ECONOMICS EDUCATION AT SENIOR HIGH SCHOOLS (Sekolah tinggi ilmu ekonomi pemuda, 2025)
Collaborative learning has become one of the most innovative approaches gaining widespread attention in modern education. This study aims to analyze the effectiveness of collaborative learning models in Economics subjects at the senior high school level. Using the Literature Review method, this research evaluates three main approaches: the Circuit Learning model, the cooperative script method, and the use of digital technology-based learning media. The findings show that the Circuit Learning model can improve students' learning outcomes, achieving an average post-test score of 85.571, significantly higher than conventional methods. The cooperative script method contributes to enhancing students' teamwork skills by 30.5%, while digital media such as augmented reality and Android applications successfully increase students' learning motivation by up to 80%. This study concludes that combining collaborative learning and digital technology can significantly improve the quality of Economics learning. Therefore, the study recommends further teacher training and the development of digital infrastructure to support the implementation of these strategies. Keywords: Collaborative learning, Circuit Learning, cooperative script, digital learning media, Economics education.